A strategic approach for building partnerships to enhance graduate employability: Driving institutional engagement - Ferns, Sonia; Le Clus, M.; Lilly, L.; Cooper, L.; Murphy, M.; Rowbottom, D.; O'Shaughnessy, A.; Sher, K.; Soh, J. (ACEN, 2014)
The student experience is enhanced through authentic learning experiences in settings that reflect the workplace. Work Integrated Learning (WIL) supports the provision of authentic learning, in a variety of contexts, within curricular and co-curricular programs, thus facilitating the development of generic skills highly sought after by employers. With increasing accountability measures facing the higher education sector and societal demands that the higher education experience prepare graduates for the dynamic environment of a global workforce, curriculum development and focus requires a paradigm shift. Curtin University values authentic learning and is committed to developing graduate capabilities through embedding WIL in all courses through scaffolding skill development across curriculum. Established partnerships and flexible arrangements with business, industry and community enable the development of professional practice to be embedded within those contexts, promoting reciprocal and mutually beneficial outcomes. The three-year WIL Strategic Project aims to enhance the employability of Curtin graduates through industry and community relationships; an experiential curriculum; and co-curricular work experience opportunities. This paper will outline the strategies implemented by the project team to achieve the University’s ambitious strategic goals; introduce innovative approaches for establishing an institutional framework; and for enhancing the student experience through WIL.